PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PT. TELKOM INDONESIA,Tbk CABANG SIDOARJO - Hadi Poernomo; hartono eka (J-MACC, 2019)
Human resources have an important role in an organization, as well as recruitment and selection that has an important role in achieving the goals of a company. This study aims to determine the effect of recruitment and selection on the performance of employees of PT.Telkom Indonesia, Tbk Cabang Sidoarjo. This study aims to: (1) Determine the effect of recruitment on employee performance of PT.Telkom Indonesia, Tbk Cabang Sidoarjo , (2) To know the effect of selection on employee performance of PT.Telkom Indonesia, Tbk Cabang Sidoarjo , (3) To know the effect of recruitment and selection together on employee performance, (4) To know which between recruitment and selection Which has a dominant effect on employee performance of PT.Telkom Indonesia, Tbk Cabang Sidoarjo. In this study using the type of quantitative research is more based on data that can be calculated to produce a solid quantitative interpretation. In this study using data analysis techniques reliabilitas test, validitas test, t test, f test and multiple regression analysis. Data analysis techniques in this study using SPSS computer apication taken from the data number of respondents. The results showed that: (1) recruitment partially affect on employee performance. This is evidenced by the value of thitung> ttable (4.568> 2.03951) with a significance value of 0.000 <0.05. (2) partial selection affects employee performance. This is evidenced by the value of thitung> ttable (3.899> 2.03951) with a significance value of 0.000 <0.05. (3) recruitment and selection affect simultaneously or simultaneously to employee performance. This can be proved by the value of Fhitungt> Ftable (124,391> 4.15) with a significance value of 0.000 <0.05. (4) recruitment is the most dominant variable influential. This can be proved by the largest regression coefficient value of 0,503 when compared with the value of regression coefficient of selection that is 0.442 and besides recruitment has the largest thitung value is 4.568 when compared with the value of thitung selection is 3.899.